Implementing evidence-based mental health practices in schools: Feasibility of a coaching strategy. Issue 4 (15th July 2019) - Koschmann, Elizabeth; Abelson, James L.; Kilbourne, Amy M.; Smith, Shawna N.; Fitzgerald, Kate; Pasternak, Anna
Abstract : Purpose: Mood and anxiety disorders affect 20–30 percent of school-age children, contributing to academic failure, substance abuse, and adult psychopathology, with immense social and economic impact. These disorders are treatable, but only a fraction of students in need have access to evidence-based treatment practices (EBPs). Access could be substantially increased if school professionals were trained to identify students at risk and deliver EBPs in the context of school-based support services. However, current training for school professionals is largely ineffective because it lacks follow-up supported practice, an essential element for producing lasting behavioral change. The paper aims to discuss these issues. Design/methodology/approach: In this pilot feasibility study, the authors explored whether a coaching-based implementation strategy could be used to integrate common elements of evidence-based cognitive behavioral therapy (CBT) into schools. The strategy incorporated didactic training in CBT for school professionals followed by coaching from an expert during co-facilitation of CBT groups offered to students. Findings: In total, 17 school professionals in nine high schools with significant cultural and socioe-conomic diversity participated, serving 105 students. School professionals were assessed for changes in confidence in CBT delivery, frequency of generalized use of CBT skills and attitudes about the utility of CBT for the school setting. Students were assessed for symptom improvement. The school professionals showed increased confidence in, utilization of, and attitudes toward CBT. Student participants showed significant reductions in depression and anxiety symptoms pre- to post-group. Originality/value: These findings support the feasibility and potential impact of a coaching-based implementation strategy for school settings, as well as student symptom improvement associated with receipt of school-delivered CBT.